Medicinal Plants of Tecopatlán, Jalisco, Mexico: Description of the Uses and Environmental Availability - Adrian Gutiérrez Alonso; Elizabeth Anne Olson; Judith Cevallos Espinosa; Jesús Juan Rosales Adame (Ethnobiology Letters, 2020)
The non-Indigenous, mestizo, ejido (communal agricultural land) Tecopatlán is located in the municipality of Autlán de Navarro, Jalisco, in the influence zone of the Sierra de Manantlán Biosphere Reserve (SMBR). The primary purpose of this research was to characterize traditional knowledge of medicinal plants held by residents of Tecopatlán in relationship to the land use patterns of the ejido. We interviewed 34 people, selected by convenience sampling, to identify their knowledge of medicinal plants and the local environment. Informants reported a total of 72 medicinal species, belonging to 45 botanical families, distributed across 67 genera. Of the plants recorded, 55 were exogenous and 19 were native species. Informants were surveyed regarding common ailments and the plants used to treat those ailments. The most common ailments reported include diabetes, coughs, kidney problems, nerves, stomach pain, insomnia, cancer, and stroke. The land use patterns described by community members reveal specific areas of the local environment that have the most commonly used medicinal plants.